Si Comind: An Innovative Web-Based Learning Platform to Enhance Students’ Learning Interest - Devy Yuliana Putri; Neni Wahyuningtyas; Ravinesh Rohit Prasad (JINoP (Jurnal Inovasi Pembelajaran), 2026)
Background: The phenomenon of digital education highlights a gap in web-based learning, where many learning platforms are still unable to optimally foster student engagement and interest, particularly in social studies, which requires interaction, collaboration, and the presentation of contextual material. This issue highlights the importance of developing digital learning platforms that not only provide content but also foster student participation and enhance interest in the learning process. Objectives: This study aims to analyze the results of the development of the Si Comind (System Collaboration of Mind) website for social dynamics content. Methods: The method used in this study is Research & Development (R&D), adopting the Rapid Application Development (RAD) model. The research subjects consisted of 31 eighth-grade students at a junior high school in Indonesia. Results: The results of the research and development of the Si Comind (System Collaboration of Mind) website received a feasibility score of 100% from subject matter experts and 96.25% from media experts. Meanwhile, the results of the pilot test with the students yielded a score of 88%. The Si Comind Website (System Collaboration of Mind) received a positive response and is highly acceptable as a social studies learning medium for eighth-grade junior high school students. Conclusions: This medium excels in presenting learning materials through various. Suggestions for future research include innovating the product in terms of media or other materials by providing interactive animations tailored to the characteristics of junior high school students and testing their effectiveness through classroom experiments.